2018
DOI: 10.1016/j.celrep.2017.11.105
|View full text |Cite
|
Sign up to set email alerts
|

winged eye Induces Transdetermination of Drosophila Imaginal Disc by Acting in Concert with a Histone Methyltransferase, Su(var)3-9

Abstract: Drosophila imaginal disc cells exhibit a remarkable ability to convert cell fates in response to various perturbations, a phenomenon called transdetermination (TD). We previously identified winged eye (wge) as a factor that induces eye-to-wing TD upon overexpression in eye imaginal discs, but the molecular mechanisms underlying TD have remained largely unclear. Here, we found that wge induces various histone modifications and enhances the methylation of Lys9 on histone H3 (H3K9), a feature of heterochromatin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Among these WiPs, we focus on Lam in this report, because there is increasing evidence that nuclear lamina proteins govern spatial genome organization in cell fate decisions (Kohwi et al., ; Poleshko et al., ; Solovei et al., ; Wen et al., ). Furthermore, we recently observed that Wge recombinant protein binds to Lam protein in vitro (Masuko et al., ). However, it is still not clear whether Wge interacts with Lam in vivo or what is the function of Lam in the TD process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these WiPs, we focus on Lam in this report, because there is increasing evidence that nuclear lamina proteins govern spatial genome organization in cell fate decisions (Kohwi et al., ; Poleshko et al., ; Solovei et al., ; Wen et al., ). Furthermore, we recently observed that Wge recombinant protein binds to Lam protein in vitro (Masuko et al., ). However, it is still not clear whether Wge interacts with Lam in vivo or what is the function of Lam in the TD process.…”
Section: Resultsmentioning
confidence: 99%
“…We then carried out mass‐spectrometric analysis of other WiPs detected as bands on SDS–PAGE (Figure a), and listed candidate WiPs (Supporting Information Table S1). It is interesting that the list included some heterochromatin regulators (Linker histone H1 [His1], Modulo and Lam), because our previous reports showed that wge affects the heterochromatin‐formation and heterochromatin‐related histone modifications (Masuko et al., ; Ozawa et al., ). His1 binds to linker DNA between nucleosomes and functions in gene silencing (Lu et al., ); Modulo is classified as a suppressor of position effect variegation (PEV) (Perrin et al., ), which involves establishment/maintenance of heterochromatin structure (Elgin & Reuter, ); Lam is a major component of the nuclear lamina on the inner nuclear membrane, and functions to regulate heterochromatin organization (Burke & Stewart, ; Van Steensel & Belmont, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally,SDS-PAGEanalysis of the reaction solution revealed that activated SPiDER-Red-bGal was bound to surrounding protein (BSA) (Figure 1d). [12] In order to confirm the applicability of SPiDER-Red-bGal for live imaging of such lacZr eporters,a sw ell as compatibility with GFP markers,weperformed ex vivo imaging of cultured live tissues of Drosophila melanogaster. This could be accomplished by our observation that disconnection of the p-conjugation is the key to trapping the fluorescent hydrolysis product inside the cells of interest, which is probably due to the appropriate generation rate and reactivity of aquinone methide intermediate.…”
mentioning
confidence: 99%